Determination of Chlorine on Brewed Robusta Coffee (Coffea canephora var. Robusta) with V60 Method - Irma Rahmawati; Yenni Puspita Tanjung (JKPK (Jurnal Kimia dan Pendidikan Kimia), 2020)
One of the manual brewing techniques is the pour-over V60 method. It uses a filter paper, which is suspected of containing chlorine as a paper bleaching agent that will dissolve in coffee. Health problems that can be caused by consuming chlorine-containing beverages in the long term can cause directly disease related to liver, bladder, intestinal cancers, arteriosclerosis, high blood pressure, pneumonia, bronchitis, dyspnea, and allergies. This study aims to determine the chlorine content of brewed robusta coffee using the brew V60 method. The chlorine test with the colour reaction method and the precipitation test as qualitative analysis to determine chlorine levels is an argentometric titration with the Mohr method. This research shows that all three samples of filter paper and coffee with V60 brewing method contain chlorine. The titration result shows that chlorine levels in filter paper brand A are 81.9 mg/L, brand B 49.9 mg/L, and brand C 69.9 mg/L. Levels of chlorine in V60 brewed coffee brand A are 44.6 mg/L, brand B 21.9 mg/L, and brand C 28.6 mg/L. This research concludes that the chlorine content in filter paper and V60 coffee brewing beverages on brand A, brand B, and brand C is unqualified according to WHO regulation about chlorine qualification for clean drinking water, which is 5 mg/L.